Didactic Teachings in Baharistan-e-Jami - Seddiqi, Zohra (Farah Research and Scientific Journal, 2025)
Didctic literature is an important branch of literature, encompassing moral, social, and scientific content. In Didactic literature, moral virtues are artistically imparted by poets and writers. Therefore, it can be said that the purpose of Didactic literature is teaching and upbringing. One of the most crucial subjects that a person needs throughout their life—and must begin learning from early childhood and continue acquiring until the last days of their life—is education and upbringing.Since education and upbringing play a fundamental and prominent role in every society, and the foundation of a healthy society is built upon the education and upbringing of its individuals, this research considers this significant and valuable issue and attempts to define the concept of education and upbringing in Baharistan-e-Jami. This study examines Baharistan-e-Jami, one of the significant works in the field of Didactic literature. Jami wrote this work, which is rich in Didactic elements, drawing inspiration from Gulistan by Saadi, as a means of offering advice and guidance to his son.The objective of this research is to analyze the role of Didactic teachings in Baharistan-e-Jami. Since this study focuses on the role of education and upbringing, particularly the Didactic teachings in this book, it holds special significance. The key question explored in this research is: What is the role of Didactic literature in Baharistan-e-Jami as an Didactic work in shaping the education and upbringing of its readers? The research methodology is descriptive-analytical and based on library studies. The findings indicate that attention to the Didactic teachings in Baharistan-e-Jami can guide readers and audiences of this work onto the right path in life, and adhering to these teachings can lead to both worldly and eternal prosperity.